Psychosocial Approaches to Child and Adolescent Health and Wellbeing - Waite-Jones, Jennifer M.; Rodriguez, Alison M. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This textbook provides an engaging guide to psychosocial theories of child and adolescents' wellbeing, demonstrating how psychology and sociology can be used to address key contemporary issues for those working with children and adolescents. It begins with an examination of the socially constructed nature of 'childhood' and 'adolescence', and impact of cultural context on the conditions for 'well-being', before outlining core psychological and sociological theories of childhood and adolescence. It adopts a psychosocial approach to illustrate the influence of social context on biologically based development in relation to topics including attachment, learning, play, parenting, family life, deviance, medicalisation, long-term conditions, vulnerability, and resilience. Through encouraging analysis of a practice-oriented case study and offering reflective questions it provides a robust introduction to how psychosocial perspectives may be applied within health, social care, and education contexts. It offers students of Social Work, Nursing, Education, Psychology and Child and Adolescent Studies the critical and theoretical tools to evaluate the interlocking psychosocial factors influencing the lives of those who will be in their care.
1. Introduction -- 2. Changing Concepts of Childhood and Adolescence -- 3. Psychosocial Theories of Childhood and Adolescence -- 4. Attachment, Parenting, and Culture -- 5. Sociability, Self-identity, and Self-esteem -- 6. Play, Learning and Developmental Wellbeing -- 7. Ambiguity within Family Life -- 8. Deviance and Labelling -- 9. Medicalisation of children and adolescents' lives -- 10. Impact of long-term conditions during childhood and adolescence -- 11. Vulnerability and Resilience in Childhood and Adolescence -- 12. Conclusion.
Keywords: Developmental psychology; Nursing; Social psychiatry; Social service; Mental health; Child and Adolescence Psychology; Nursing; Clinical Social Work; Social Work; Mental Health; Children and Youth Work